Mechanical Behavior and Chloride Penetration of Precracked Reinforced Concrete Beams with Externally Bonded CFRP Exposed to Marine Environment - Yan Xie; Kunhua Guan; Lei Zhan; Qichen Wang (International Journal of Polymer Science)
Cracked reinforced concrete (RC) beams can be repaired effectively by using externally bonded CFRP sheets. However, when the strengthened beams are subjected to marine environment, long-term performance will be affected by the material and the interface deterioration of concrete and CFRP. Therefore, to evaluate the service life of the strengthened beams, this study investigates the behavior of precracked RC beams strengthened with CFRP sheets exposed to marine environment. Accelerated ageing experiments were carried out by exposing specimens to cyclic wetting in sea water and drying in 40°C air for 3 months and 6 months, respectively. After the environment exposure, four-point bending test was conducted and then the diffusion of chlorides in the strengthened beams was analysed. The results show that the bonding behavior of the adhesive was weakened and the ductility of the strengthened beams was slightly reduced due to the marine environment. But there is no obvious strength difference between the strengthened beams suffered from marine environment for 3 months and 6 months. Besides, the precracks in the RC beams accelerated the chloride diffusion, while CFRP bonding reduced the chloride penetration. In addition, NEL method was employed to validate the effect of the cracks on chloride permeability. The results showed that the chloride diffusion coefficients increased with the depth of the cracks.